Togo – 2010: Domestic politics, foreign affairs, and socio-economic development - Dirk Kohnert (Africa Yearbook Volume 7: Politics, Economy and Society South of the Sahara in 2010, 2011)
Non-violent presidential elections paved the way for another five-year mandate for Faure Gnassingbé in Togo in 2010. Although marked by considerable irregularities, the voting was considered largely credible by the international community, which enhanced the legitimacy of the incumbent. An important cause of the defeat of the major opposition party was the growing internal divide between the `old guard' and the `young Turks', which led to a split in the `Union des Forces du Changement' (UFC). Its leader Gilchrist Olympio, the generation-long adversary of the Gnassingbé regime, saw his hopes dashed and entered the government of national reconstruction, while the party's presidential candidate, together with the majority of its faction within the UFC founded a new radical opposition group. The EU and the international community followed a `laissez-faire' approach in the interests of stability and their own national interests in dealings with the country. A World Bank review of the economy revealed a remarkable shift in exports caused by the ailing phosphate and cotton sectors, along with an enduring lack of good governance. – – Gewaltfreie Präsidentschaftswahlen ebneten 2010 den Weg für eine weitere fünfjährige Amtszeit von Faure Gnassingbé in Togo. Obwohl die Wahlen von erheblichen Unregelmäßigkeiten geprägt waren, wurden sie von der internationalen Gemeinschaft als weitgehend glaubwürdig angesehen, was die Legitimität des Amtsinhabers stärkte. Eine wichtige Ursache für die Niederlage der größten Oppositionspartei war die wachsende interne Kluft zwischen der ,,alten Garde“ und den ,,Jungtürken“, die zu einer Spaltung der ,,Union des Forces du Changement“ (UFC) führte. Ihr Vorsitzender Gilchrist Olympio, der Generationen lang Gegner des Gnassingbé-Regimes war, sah seine Hoffnungen enttäuscht und trat der Regierung des nationalen Wiederaufbaus bei, während der Präsidentschaftskandidat der Partei zusammen mit der Mehrheit seiner Fraktion innerhalb der UFC eine neue radikale Oppositionsgruppe gründete. Die EU und die internationale Gemeinschaft verfolgten im Interesse der Stabilität und ihrer eigenen nationalen Interessen im Umgang mit dem Land einen ,,Laissez-faire“-Ansatz. Eine Untersuchung der Weltbank zur wirtschaftlichen Lage ergab eine bemerkenswerte Verschiebung der Exporte, die durch die schwächelnden Phosphat- und Baumwollsektoren sowie einen anhaltenden Mangel an guter Regierungsführung verursacht wurde.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2010; domestic policy; foreign affairs; socio-economic development; period under review 2010